LITERASI DIGITAL DAN ETIKA MEDIA SOSIAL DI ERA POST-TRUTH - Rianto, Puji (Interaksi: Jurnal Ilmu Komunikasi, 2019)
This research is an attempt to explain the post-truth phenomenon in the WhatsApp group. This research, therefore uses online etnography or netnography, it found that the widespread post-truth in the WhatsApp group marked by the spread of hoax is not mere caused by a lack of digital literacy, but rather an ethics. The fact that conversation groups are able to analyze, and evaluate political messages, but uncritical when dealing with political messages that support their political choices (candidates). As a result, they tend to believe on what they might think as thruth, even with no clarifying wheather it’s true or false. In such case, they even deliberately and consistently to share any information even though other group providing correction for many times. This research, therefore suggests that digital literacy must be integrated with communication ethics. In regard with digital literacy, indeed it’s very necessary to enhance the critical capabilities of digital media users, while ethics lead people to always think and consider the good or bad of the communication activities.